Community Composition of Nitrous Oxide Consuming Bacteria in the Oxygen Minimum Zone of the Eastern Tropical South Pacific - Sun, Xin; Jayakumar, Amal; Ward, Bess B. (Frontiers in Microbiology, 2017)
The ozone-depleting and greenhouse gas, nitrous oxide (N2O), is mainly consumed by the microbially mediated anaerobic process, denitrification. N2O consumption is the last step in canonical denitrification, and is also the least O2 tolerant step. Community composition of total and active N2O consuming bacteria was analyzed based on total (DNA) and transcriptionally active (RNA) nitrous oxide reductase (nosZ) genes using a functional gene microarray. The total and active nosZ communities were dominated by a limited number of nosZ archetypes, affiliated with bacteria from marine, soil and marsh environments. In addition to nosZ genes related to those of known marine denitrifiers, atypical nosZ genes, related to those of soil bacteria that do not possess a complete denitrification pathway, were also detected, especially in surface waters. The community composition of the total nosZ assemblage was significantly different from the active assemblage. The community composition of the total nosZ assemblage was significantly different between coastal and off-shore stations. The low oxygen assemblages from both stations were similar to each other, while the higher oxygen assemblages were more variable. Community composition of the active nosZ assemblage was also significantly different between stations, and varied with N2O concentration but not O2. Notably, nosZ assemblages were not only present but also active in oxygenated seawater: the abundance of total and active nosZ bacteria from oxygenated surface water (indicated by nosZ gene copy number) was similar to or even larger than in anoxic waters, implying the potential for N2O consumption even in the oxygenated surface water.